Sustainable development as freedom: Trends and opportunities for the circular economy in the human development literature - Lima, Pedro A. B. [UNESP]; Jesus, Gessica M. K. [UNESP]; Ortiz, Camila R. [UNESP]; Frascareli, Fernanda C. O. [UNESP]; Souza, Fernando B. [UNESP]; Mariano, Enzo B. [UNESP] (MDPI, 2021)
This paper identifies, through a literature review, how 53 circular economy (CE) practices are related to the capability approach (CA) proposed by Sen. The main goal was to identify how a virtuous cycle between CE and CA can be developed. Five instrumental freedoms (IF) were analysed: economic facilities, social opportunities, protective security, political freedoms, and transparency guarantees. These relationships were analysed in three flows: CE practices positively impacting IF, CE practices negatively impacting IF, and the feedback influence of IF on CE practices. The results show that 32 of the 53 practices previously mentioned have not yet been studied from the CA context, which indicates that there are several research opportunities. From the practices considered, 72 articles were analysed in the final sample. The results suggest that several CE practices are aligned with the CA, considering that all five IF were identified as positive outcomes of CE practices. However, in some contexts, certain practices can have negative outcomes, which indicates that CE, at least in some cases, may not be considered as sustainable, as it decreases IF and, therefore, the social aspect of sustainability. The results also highlight that there is a feedback from IF to CE, in such a way that investing in the expansion of IF can facilitate the development of CE practices. Therefore, this study concludes that CE is indeed a way to fully operationalize sustainable development.
Keywords: Capability approach; Circular economy; Human development; Instrumental freedoms; Sustainable development; Virtuous cycle